Target-controlled infusions of butorphanol worsen hemodynamics in isoflurane-anesthetized cats - Pypendop, Bruno H.; Cenani, Alessia; Machado, Marcela L.; Barter, Linda S. (Frontiers in Veterinary Science, 2025)
IntroductionPartial intravenous anesthesia can be used to reduce the adverse effects of inhalant anesthetics, and opioids are often used in this context in dogs and cats. The opioid butorphanol was recently shown to dose-dependently reduce the minimum alveolar concentration of isoflurane in cats. The aim of this study was to characterize the hemodynamic effects of butorphanol in isoflurane-anesthetized cats.MethodsSix cats were anesthetized with isoflurane and administered butorphanol to maintain target plasma concentrations (TPCs) of 0, 1.1, 2.2 and 4.4 μg mL−1, with or without concurrent administration of atropine. The isoflurane concentration was adjusted to maintain equipotency based on the results of a previous study. Cardiorespiratory variables were measured at each plasma butorphanol concentration.ResultsSevere bradycardia and hypotension were observed in one cat at the 4.4 μg mL−1 TPC and in one cat at the 2.2 μg mL−1 TPC without atropine. Treatments without atropine and the 4.4 μg mL−1 TPC were not studied in subsequent cats. Butorphanol significantly reduced heart rate, cardiac index and oxygen delivery index, and increased systemic vascular resistance index and oxygen consumption index in a plasma concentration-dependent manner.DiscussionIn isoflurane-anesthetized cats, at the TPCs studied, butorphanol caused more cardiovascular depression than a higher, equipotent concentration of isoflurane alone.